La incapacidad de la mujer casada y su superación en El Código Civil español (2018)
The 1889 Spanish Civil Code reflected the marginalization of women through diverse discriminatory provisions that were founded on the idea of women’s alleged weakness and need for protection, equating women with minors or incapacitated people. Thereafter, the Spanish Civil Code has undergone a long and difficult journey full of successive reforms that have contributed to a satisfactory ascent of women in Civil Law. This article focuses on four concepts: the legal situation of women in the nineteenth century, women’s struggle for equality in the Second Republic, the Francoist model and the legal concept of women, and the arrival of democracy in Spain. Together, these four elements are a tool to understand the legal status of women in Spain. This article is divided into five sections: the first studies the definition of women when the Spanish Civil Code of 1889 was enacted, its legislative application to women and its legal concept; the second one examines how the legal concept of women changed in the Second Republic through the foundation of the feminist movement; the third analyzes changes in the concept of women in the Franco era with the disappearance of egalitarian rights and causes of separation; the fourth presents the promulgation of the Spanish Constitution in 1978 and the arrival of democracy that reestablished the equal concept of men and women in marriage, while the fifth section addresses the causes of separation in the current Spanish context and the evolution of marriage